Domestic Violence and Women’s Legal Awareness: The Family Corner Programmes Interventions through the Perspective of Maqāṣid al-Usrah - Cholil, Mufidah; Rouf, Abd.; Rahmatullah, Prayudi; Ni’ami, Mohammad Fauzan (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2025)
This study examines the mosque-based family corner in Malang Regency as a community institution implementing a legal awareness intervention programme for victims of domestic violence. The research specifically analyses the design and implementation of this intervention through the perspective of Jamaluddin Athiyyah’s maqāṣid al-usrah, while also evaluating key programme components such as legal education, counselling, mediation, and legal advocacy aimed at enhancing victims’ legal awareness. Employing field research with a descriptive-qualitative approach, data were collected through in-depth interviews with family corner counsellors, religious figures, and community leaders, complemented by direct field observations of programme activities. The findings demonstrate that the mosque-based family corner plays a significant role in assisting families affected by domestic violence, particularly by increasing victims’ understanding of their legal rights and encouraging informed decision-making through non-litigation mechanisms. The intervention programme contributes positively to strengthening family integrity, restoring communication, and fostering a shared commitment to preserving family unity following incidents of domestic violence. These outcomes are consistent with the core objectives of Jamaluddin Athiyyah’s maqāṣid al-usrah, including the realisation of sakinah, mawaddah, and rahmah within the family; the protection of life (ḥifẓ an-nafs); the safeguarding of religious values (ḥifẓ at-tadayyun); and the reinforcement of family institutions as a foundation of social stability. This study enriches the scholarly discourse on legal awareness among women victims of domestic violence, particularly those who choose counselling-based, non-litigation pathways, and highlights the strategic role of mosque-based community institutions in promoting access to justice and family resilience.